2015
DOI: 10.1590/1679-78251520
|View full text |Cite
|
Sign up to set email alerts
|

Effects of material properties on generation of brake squeal noise using finite element method

Abstract: This research paper is concerned with the disc brake squeal problem for passenger cars. The aim of the present research is developing a finite element model of the disc brake assembly in order to improve understanding of the influence of Young's modulus on squeal generation. A detailed finite element model of the whole disc brake assembly that integrates the wheel hub and steering knuckle is eveloped and validated using experimental modal analysis. Stability analysis of the disc brake assembly is accomplished … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…The results of rule of mixture formulation indicate that the coconut shell-reinforced composite has a theoretical density of 1.073 g/cm 3 . This predicted value of the brake pad composite is in good agreement with recommended values of commercial brake pad whose densities fall between 1.010 and 2.060 g/cm 3 as reported by Abutu et al [18] and Efendy et al [25].…”
Section: Formulation Of Samples Using Rule Of Mixturementioning
confidence: 99%
See 1 more Smart Citation
“…The results of rule of mixture formulation indicate that the coconut shell-reinforced composite has a theoretical density of 1.073 g/cm 3 . This predicted value of the brake pad composite is in good agreement with recommended values of commercial brake pad whose densities fall between 1.010 and 2.060 g/cm 3 as reported by Abutu et al [18] and Efendy et al [25].…”
Section: Formulation Of Samples Using Rule Of Mixturementioning
confidence: 99%
“…This system consists of three major parts which include the brake pad, rotor and caliper [1,2]. Belhocine and Nouby [3] revealed that braking system is one of the most fundamental safety components in modern passenger cars as it is significant in stopping or slowing down of vehicles. Brake pads are used in the braking and transmission of various machinery as well as equipment such as aircraft, cars, motorcycles and other automobile vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…Brake squeal phenomenon induces under-quality perception for industrial structures such as cars and trains, and its understanding is an important challenge [1,2,6,7,9,14]. Understanding squeal noise requires the analysis of brake systems from a "vibration and acoustics" point of view.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical approaches have thus been used to study on the wear of the seal. Due to the widely used of Finite element method (FEM) in the structural analysis [ 24 ], a combination of the FEM and Archard wear model is normally adopted to simulate the seal wear [ 25 ]. The contact pressure is calculated by finite element analysis (FEA).…”
Section: Introductionmentioning
confidence: 99%